In vitro Propagation of an Ornamental Bamboo (Bambusa tuldoides Munro) - Sharothi, Partho; Raju, Raihan Iqbal; Hossain, Mohd Talim (Plant Tissue Culture and Biotechnology, 2022)
This study was undertaken to standardize an efficient protocol for in vitro propagation of an ornamental bamboo Bambusa tuldoides Munro using nodal segments as explants. For direct shoot induction, liquid MS medium containing 2.0 mg/l BAP and 1.0 mg/l TDZ gave a maximum response (84%) with maximum number of shoots (4.80 ± 0.49) per explant. These shoots were proliferated efficiently on agitated liquid MS medium with 3.0 mg/l BAP and 1.5 mg/1 TDZ, which resulted in the formation of 15.40 ± 1.21 shoots per culture with 6.96 ± 0.65 cm shoot length. Shoots gradually increased in number and length during the first four subculture cycles in the same media combination but declined in 5th sub-culture cycle. After the 4th sub-culture cycle, the number of shoots per culture was 20.40 ± 1.44 and shoot length was 7.92 ± 0.78 cm. The addition of 10% coconut water with the above mentioned medium resulted in satisfactory shoot growth and development with 24.20 ± 1.16 shoots per culture. Maximum (84%) rooting with the highest number of roots per culture (7.20 ± 0.37) was obtained from half-strength MS medium fortified with 3.0 mg/l IBA. Well rooted plantlets were successfully acclimatized to the soil where the survival rate was 92%. Plant Tissue Cult. & Biotech. 32(2): 157-166, 2022 (December)